2015
DOI: 10.1038/srep17233
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria Protects Caenorhabditis elegans from Toxicity of Graphene Oxide by Maintaining Normal Intestinal Permeability under different Genetic Backgrounds

Abstract: Lactic acid bacteria (LAB) is safe and useful for food and feed fermentation. We employed Caenorhabditis elegans to investigate the possible beneficial effect of LAB (Lactobacillus bulgaricus) pretreatment against toxicity of graphene oxide (GO) and the underlying mechanisms. LAB prevented GO toxicity on the functions of both primary and secondary targeted organs in wild-type nematodes. LAB blocked translocation of GO into secondary targeted organs through intestinal barrier by maintaining normal intestinal pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…[57] In addition, food matrix effects have been shown to modulate the bioactivity of ENMs, [32,35] and the gut microbiome and proteome of animals is known to be sensitive to the presence of chemically active particulates. [28,29,60] Therefore, we plan to apply the methods developed here to interrogate the physicochemical transformations, toxicological assessment, and effect on gut microbiome and proteome of GO in the presence of more complex food models.…”
Section: In Vitro Toxicological Assessment Of Small Intestinal Go Digmentioning
confidence: 99%
“…[57] In addition, food matrix effects have been shown to modulate the bioactivity of ENMs, [32,35] and the gut microbiome and proteome of animals is known to be sensitive to the presence of chemically active particulates. [28,29,60] Therefore, we plan to apply the methods developed here to interrogate the physicochemical transformations, toxicological assessment, and effect on gut microbiome and proteome of GO in the presence of more complex food models.…”
Section: In Vitro Toxicological Assessment Of Small Intestinal Go Digmentioning
confidence: 99%
“…Tissue-specific activity assay has demonstrated the important functions of DAF-16 in regulating longevity in the intestine and neurons of nematodes30. Interestingly, our previous study has suggested that mutation of sod-3 gene resulted in a susceptible property of nematodes to GO toxicity on lifespan, reproduction, and locomotion behavior, and induced a more severe induction of ROS production in GO exposed nematodes1921. In the present study, we employed an in vivo assay system of C. elegans to investigate the possible involvement of insulin signaling pathway in the control of GO toxicity and its potential molecular mechanisms.…”
mentioning
confidence: 98%
“…Regarding the cellular mechanisms of GO toxicity, the published data have suggested that GO toxicity might be consequent to the bioavailability, induction of reactive oxygen species (ROS), enhanced intestinal permeability, disrupted innate immune response, and prolonged defecation cycle length in nematodes16171920. Previous studies have also implied the crucial role of intestinal biological barrier against GO toxicity in nematodes1721. It has also been reported that the induction of oxidative stress might play a key role in the chemical mechanism for GO induced shortened longevity in exposed nematodes15.…”
mentioning
confidence: 99%
“…To investigate the in vivo translocation and distribution of GO, Rho B was loaded on the GO by mixing Rho B solution (1 mg/mL, 0.3 mL) with aqueous GO suspension (0.1 mg/mL, 5 mL) as described58. The unbound Rho B was removed by dialysis against the distilled water over 72 h. The finally resulting GO/Rho B was stored at 4 °C.…”
Section: Methodsmentioning
confidence: 99%